Penderitaan Dalam Novel Tiba Sebelum Berangkat Karya Faisal Oddang - Oscar Randa; Muhammad Adek (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to describe: (1) the forms of suffering in Faisal Oddang's Tiba Sebelum Berangkat novel, (2) the causes of suffering in Faisal Oddang's Tiba Sebelum Berangkat novel, (3) how to overcome suffering in Faisal Oddang's Tiba Sebelum Berangkat novel. The object of this research is the novel Tiba Sebelum Berangkat by Faisal Oddang which was published in 2018. This research uses a descriptive method. The data of this research are in the form of words, phrases, clauses and sentences related to forms, causes, and ways of overcoming suffering and in the form of narrator exposure, character speech, character actions contained in the novel Arriving Before Leaving by Faisal Oddang. The research instrument in this study was the researcher himself as the main instrument using a number of formats, both for data collection and for analyzing data. The data collection techniques used in this study were reading and understanding the novel, marking the narratives of the characters and narrators in the novel that match the data sought or needed, identifying data related to the research problems contained in the novel Tiba Sebelum Berangkat by Faisal Oddang . The data analysis technique used in this study is to identify data about Mapata's suffering contained in the novel, analyze the data obtained, draw conclusions about the problems contained in the novel and write it in the form of a research proposal. The results of this study are: (1) forms of suffering, consisting of 3 forms, namely: (a) suffering as pain, (b) suffering as a change, (c) suffering as a condition. (2) causes of suffering, consisting of 3 causes, namely: (a) sensory/sensual desire, (b) desire for existence, (c) desire for non-existence. and (3) how to overcome suffering, consisting of 3 ways, namely: (a) right speech, (b) right effort, (c) right thought.